Early treatment with isoflurane attenuates left ventricular dysfunction and improves survival in experimental Takotsubo. Issue 4 (10th February 2017) - Oras, J.; Redfors, B.; Ali, A.; Alkhoury, J.; Seeman‐Lodding, H.; Omerovic, E.; Ricksten, S.‐E.
Abstract : Background: Takotsubo syndrome (TS) is an acute cardiac condition, often triggered by critical illness, for which no specific treatment exists. Previously, we showed that isoflurane can prevent experimental TS. The aim of this study was to evaluate the potential treatment effects of isoflurane. Our primary hypothesis was that early treatment with isoflurane attenuates left ventricular akinesia in experimental TS. Method: In propofol‐sedated animals, TS was induced by an intraperitoneal bolus of isoprenaline (50 mg/kg). Animals were randomized to one of six groups ( n = 15 in each group), and 1% isoflurane was administered for 90 min in all groups. Isoflurane treatment was started at 0, 10, 30 (early treatment) or 120 (late treatment) minutes after isoprenaline injection. One additional late treatment group received isoflurane 0.5% for 180 min. A control group did not receive isoflurane. Left ventricular (LV) echocardiographic examination was performed at 90 min and 48 h after isoprenaline. Mortality was assessed at 48 h. Results: Median degree of LV akinesia at 90 min was 24% in the control group and 0% in the early treatment groups ( P < 0.001). Stroke volume, cardiac output and LV ejection fraction were higher in the early treatment groups vs. controls ( P < 0.01). Mortality was lower in the early treatment groups (24%) vs. controls (86%) ( P < 0.001). Mortality did not differ between the late treatment groups and controls. Conclusion: Early treatment with isoflurane attenuates the LV akinesia and improves survival in experimental TS. Isoflurane sedation in patients at risk of developing Takotsubo syndrome could be a subject for future studies.